Regarding the Reception of the Stalinist Plan for the Transformation of Nature in Hungary, Czechoslovakia and Poland - Jarosz, Dariusz (Kwartalnik Historyczny, 2018)
Originating in nineteenth-century scientism, the effort to control and transform nature was an important part of the communist ideology. This article deals with the implementation of the Stalinist plan for the transformation of nature in Poland, Czechoslovakia and Hungary.